Financing R & D with Knowledge Stock Rentals - John M. Hartwick (Queen's University, Department of Economics, 1993)
We set out an endogenous growth model along the lines of Romer(1990) and investigate the implications of financing new knowledge production (R&D) with rental income accruing to the knowledge stock used in goods production. The knowledge stock is a non-public input in goods production. The balance growth rate under optimal growth can be greater or less than that under the invest knowledge stock rentals regime depends on the parameters of the production function and not on the parameters of preference.
Keywords: 330